The landmarks of control and licensing system development for medicinal products in Russia (25 years since the establishment of the first state institution for expert evaluation of medicinal products) - V. K. Lepakhin; Yu. V. Olefir; V. A. Merkulov; N. D. Bunyatyan; B. K. Romanov; A. N. Yavorsky; E. M. Rychihina (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article describes the landmarks of control and licensing system development for the purpose of drug evaluation, marketing authorization and circulation in Russia. The need for the development of a state institution for performing expert evaluation of medicines was satisfied in 1990 by the establishment of the All-Soviet Union Scientific Centre for Expert Evaluation of Medicines (renamed in 1992 as the Russian State Centre for Expert Evaluation of Medicines - RSCEEM). The activities of the Centre included expert evaluation of all documents for new pharmaceutical products; organization and monitoring of clinical trials, as well as the assessment of their results; development of the recommendations regarding marketing authorization and medical use of new medicines. It also exercised the functions of the Federal Centre for Adverse Drug Reaction Study. RSCEEM became a basis for modern currently functioning Scientific Centre for Expert Evaluation of Medicinal Products».